Attachment disorganization moderates the effect of maternal postnatal depressive symptoms on infant autonomic functioning. (18th December 2012) - Tharner, Anne; Dierckx, Bram; Luijk, Maartje P.C.M.; van, Marinus H.; Bakermans‐Kranenburg, Marian J.; van, Joost R.; Moll, Henriette A.; Jaddoe, Vincent W.V.; Hofman, Albert; Hudziak, James J.; Verhulst, Frank C; Tiemeier, Henning
Abstract We examined associations of disorganized attachment and maternal depressive symptoms with infant autonomic functioning in 450 infant‐mother dyads enrolled in the Generation R study. Maternal depressive symptoms were measured 2 months postpartum with the Brief Symptom Inventory. At 14 months, we assessed infant attachment with a slightly shortened Strange Situation and measured infant resting heart rate. Respiratory sinus arrhythmia (RSA) was calculated using spectral analysis. Higher levels of maternal postnatal depressive symptoms predicted lower resting RSA in disorganized infants (B = −0.31, SE = 0.15, p = .04, R2 = .05) but not in nondisorganized infants (B = 0.05, SE = 0.06, p = .36). This effect was buffered in disorganized infants with a secondary secure attachment classification. Disorganized infants were more vulnerable to the effect of maternal postnatal depressive symptoms on the physiological stress systems.